DNA availability from fly maggots infesting on varied beef meat conditions - Heimkumar, Veerayutharani (2022)
The aim of this research was to identify the availability of meat DNA that is available from fly maggots that has been feeding on beef meat. This research was carried out to determine which stage of the fly maggots are a suitable option for the DNA extraction and analysis of meat DNA. By extracting DNA from the fly maggots, the field of forensic entomology and forensic biology can be used together to identify victim cadavers when the maggots are not being used for PMI estimation or when the victims’ body is not suitable for identification. In this study, three conditions of beef meat were placed at three different field location concurrently and the first instar, second instar and third instar maggots were collected. At the same time, the beef meat samples were also collected. Unfortunately, the dried beef meat sample had to be excluded due to the absence of flies and maggots on the meat up to two weeks from the initial set-up. The results showed that the concentration of nucleic acid is generally higher in the meat samples compared to the maggots except for the first instar maggots. The high nucleic acid concentration in the first instar maggot is most probably due to the presence of maggot DNA as more maggots were used for the first instar maggot DNA extraction compared to the second and third instar maggots. After PCR amplification using the bovine cytochrome B primer, the target gene was successfully amplified for the second and third instar maggots from the fresh beef meat sample. In contrast, the target gene was not successfully amplified for the maggots from the frozen beef meat condition. In conclusion, the second and third instar maggots can be used for the DNA extraction when the meat is fresh, and more research must be done for the frozen meat and dried meat on the DNA availability.